Workshop: Adopting PBL – Hybrid in Resource Constraint Settings: Perspectives from Gulu University - Dirckinck-Holmfeld, Lone; Tabo, Geoffrey Olok; Bygholm, Ann; Camacho, Heilyn Nunez; Drateru, Vivian Perry; Canwat, Vincent; Jensen, Iben; Kansiime, Clara; Kamakech, Walter; Namubiru, Margaret; Pakono, David Okot; Olanya, David Ross (Proceedings of the International Conference on Networked Learning, 2026)
The PBL-Hybrid project, a collaboration between Gulu University and Aalborg University under the Building Stronger Universities initiative, addresses the urgent need for flexible, student-centred education in fragile contexts. Inspired by the persona of Mr. Okot—a working professional facing long travel times to pursue higher education—the project responds to challenges intensified by the Covid-19 pandemic and the broader socio-economic realities of northern Uganda. The novelty of the project lies in the integration of problem-based learning (PBL), design thinking, and digital technologies to create hybrid learning models that support both academic and community transformation. Using the Student-Centred eLearning Implementation Methodology (S-C eLIM), the project follows five phases: Envisioning, Preparing, Piloting, Scaling, and Maturing. It has been piloted across three Master's programmes at Gulu University, engaging over 300 students. The methodology promotes sustainable change by empowering students and facilitators to become active agents in their learning environments. Design thinking fosters creativity, interdisciplinary collaboration, and real-world problem solving, while technology enhances flexibility and accessibility. The results demonstrate significant shifts in teaching and learning practices. Facilitators and students now co-create learning experiences that link theory with practice, address community challenges, and build 21st-century skills. Despite limited material resources, the project showcases the power of human capacity when supported by innovative pedagogical frameworks. In conclusion, the PBL-Hybrid project exemplifies how higher education in resource constrained context can adapt to post-pandemic realities by embracing inclusive, participatory, and technology-enhanced approaches. It offers a replicable model for universities in similar contexts, aiming to transform education into a tool for resilience, empowerment, and sustainable development.